Authoritarian rule of law legislation, discourse, and legitimacy in Singapore - Rajah, Jothie (Cambridge studies in law and society, 2012)
This book presents an analysis of authoritarian legalism, showing how prosperity, public discourse, and a rigorous observance of legal procedure enable a reconfigured rule of law - liberal form but illiberal content. It shows how institutions and process become tools to constrain dissenting citizens while protecting those in political power.